Estimated Foetal Weight Versus Abdominal Circumference in Predicting Adverse Outcome in Foetal Growth Restriction - Lydia DeAngelo‐Lewis; Justin Moore; Meng Yao; Catherine Klammer; Sarah Graves; Lauren Buckley; Oluyemi Aderibigbe; Amol Malshe; Maeve Hopkins (Reproductive, Female and Child Health, 2025)
ABSTRACT Objective To identify foetal growth restriction (FGR) based on estimated foetal weight (EFW) < 10th percentile, abdominal circumference (AC) < 10th percentile or both EFW and AC < 10th percentile. To determine which group(s) is associated with a higher risk for adverse neonatal outcomes in singleton FGR pregnancies. Study Design Retrospective cohort study of singleton deliveries with prenatal FGR diagnosis at a single tertiary hospital system 1/1/2021–12/31/2021. FGR was defined as: EFW < 10th percentile only (EFW group), AC < 10th percentile only (AC group), or both EFW/AC < 10th percentile at initial diagnosis (EFW/AC group). The primary composite neonatal outcome includes urgent caesarean section delivery, APGAR < 6 at 1 or 5 min, NICU admission, stillbirth, or neonatal death. Results A total of 647 patients met inclusion criteria (EFW: 168, AC: 139, EFW/AC: 340) and no differences were observed in maternal demographics between groups. The composite neonatal outcome occurred at a higher frequency in EFW (36.3%) and EFW/AC (37.8%) groups compared to AC group alone (22.3%) (p = 0.004). Gestational age at delivery in days was earlier in EFW/AC group (264 [258, 273]) compared to EFW (267 [259, 273]) and AC (269 [264, 274]) groups (p < 0.001). Although not reaching statistical significance, there was higher rate of preeclampsia with severe features in the EFW/AC group (20%) compared to the EFW (13.1%) or AC groups (13.7%) (p = 0.078). Conclusions EFW and EFW/AC groups were associated with a higher risk of adverse neonatal outcomes compared to the AC group. Delivery occurred earlier in pregnancies diagnosed with FGR based on EFW and EFW/AC compared to the AC group. These findings can inform risk counselling in pregnancies diagnosed with FGR.